Tryptophan requirements for body and feather growth of broilers as affected by breed, sex, weight interval and dietary protein level - Cilliers, Stefanus Christiaan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1990.